An Aggressive Strategy for Asia Commercial Finance (M) Bhd - P. Muttu, Kumar (1999)
Asia Commercial Finance (M) Berhad (ACF) has been in business for more than 30 years and it offers wide range of financial products. Over the years the company has shown a steady growth in its business, although need to compete with 39 other finance companies in Malaysia. The prospect of ACF as finance company is encouraging due to: i) The need for financial assistance by productive sectors in the country. ii) The hire purchase facility still remains as important factor in automobile industry iii) Increased in South East Asia's trading activities. Recently, Bank Negara Malaysia (BNM) imposed 8% credit growth For all financial institutions in Malaysia by end of 1999. The performance of ACF is diminishing instead of improving. The branch managers were forced to market the company's financial products aggressively. But, the branches are unable to capture more market share due to aggressive strategies of it's competitors. The management of ACF need to adopt prudent practice in approving loans, thus not resulting in poor credit decisions. The asset quality of ACF is deteriorating, therefore the company enhanced the lending activities. On the other hand the rigidity of the management becomes the barrier for lending expansion. In order for the company to improve its asset quality and capture more market share, the most appropriate strategy is to merge with other financial institutions and subsequently to improve the company's asset quality. The company also will able to compete with foreign financial institutions when government liberalize the sector.